Handcrafting Joy to Support Both the Patient and Clinician Experience - Noor Fathima Shaik MD, PhD; David Do MD; Roy Rosin MBA (Journal of Patient Experience)
A patient's hospital stay is too often wrapped in fear and worry. Healthcare leaders have emphasized the immense need to improve patient experience and address patients’ individual needs. In addition to helping with the medical aspect of healing, we believe health systems can encourage and empower providers to perform acts of kindness to help elevate the otherwise stressful experience of being hospitalized. We describe an initiative focused on tailoring joyful surprises, like unexpected gifts, to help support both patients and clinicians, aiming to improve patient experience and satisfaction while reducing provider burnout. In sharing the stories of the interactions between the providers and patients, it is clear that not only has this program brought joy to our patients, but that it has also helped reconnect our providers with their sense of meaning and purpose in caring for people and meeting their needs. Thus, we herein describe a patient-centered initiative that enables healthcare providers to provide unique and joyful surprises for their patients in a manner that is readily scalable, cost-effective, accessible, and deeply impactful.